Research on the Effect of Rare Earth on the Structure and Impact Performance of Armor Steel. Issue 1 (March 2021) - Zhang, Mingyi; Gao, Ping; Luo, Guoping; Geng, Wenyuan; Jia, Xiaobin
Abstract: In order to study the impact performance of 685 armored steel with different mischmetal content, the impact performance of the steel at room temperature and -40°C was tested, and the impact fracture morphology and microstructure were observed and analyzed. The results show that the addition of mixed rare earth La-Ce to the test steel improves the tempered martensite structure and refines the austenite grains. At the same time, the inclusions in the steel are modified, and the elongated MnS inclusions are modified. It is a spherical composite rare earth inclusion, and the size of the inclusion is reduced from 6 μ m to 2 μ m. Compared with the test steel without rare earth, the room temperature impact performance of the mixed rare earth test steel and the -40 °C low temperature impact performance are improved. When the La-Ce content is 102 × 10 −6, the room temperature impact energy of the protective steel increases by 24.5%, and the low temperature impact energy at -40 °C increases by 17. 4%. The results of the shooting test showed that the protection level of rare earth-containing armored steel reached NATO Level 2.